Grammar Book Based on Games for Fifth Grade of MI Kebokicak Jombang - Afidah, Nurul; Zulfa, Garhana; Ma'arif, Iin Baroroh (JoEMS (Journal of Education and Management Studies), 2022)
In MI Kebokicak, teaching learning still used the usual method without media and was still lack of facilities and infrastructure. Eventhough learning media was eded to facilitate teachers in transferring knowledge and making it easier for students to understand English material. Therefore, the purpose of this study was to develop Grammar Book based on Games to help fifth grade students at MI Kebokicak. The research method used was Research and Development, this development used ADDIE learning model which consisted of five steps, those were: 1) Analyze, 2) Design, 3) Development, 4) Implementation, and 5) Evaluation. The results of this assessment indicated that the Grammar Book based on Games media had “very good” feasibility, according to media expert getting an average of 83.33 and material expert 73.33. Subject of this research was students of fifth grade students at MI Kebokicak Jombang. The students responses of try out result 84.8 which that meant this learning mediagood category. It can be concludeammar Book based on Games feasible was ready to use.